The role of active music making in fostering resilience - Heck, Pauline Sophie; Reinhardt, Wiebke; Bischoff, Andrea; Koelsch, Stefan (Frontiers in Neuroscience, 2025)
Previous studies suggest a positive association between engagement with music and psychological resilience, yet most existing research has focused on specific populations or isolated aspects of musical activity or resilience. The present study addresses this gap by examining the relationship between musical sophistication and resilience in a diverse adult sample recruited across several countries. An online survey was conducted with 392 healthy participants and 84 individuals with depression. Musical sophistication was assessed with the Goldsmiths Musical Sophistication Index (Gold-MSI), and resilience was measured using two validated scales (CD-RISC and BRS). Partial correlations in the healthy sample showed that musical sophistication was positively associated with resilience as measured by the CD-RISC, but not by the BRS. Contrary to the notion that individuals with depression may benefit less from music as a resilience resource due to maladaptive engagement patterns, we observed a positive – and even stronger – correlation with both resilience measures in this group. Further analyses revealed that among healthy individuals, active musical behaviours (such as making music or dancing) were more strongly associated with resilience than passive engagement (listening only). Both healthy and depressive participants reported feeling calmer and more peaceful after using music to cope with stress; this effect was significantly more frequent in the depressive group, particularly in the context of coping with depressive symptoms. Although the correlational design precludes causal conclusions, the findings suggest that musical sophistication is positively related to resilience, in both healthy and depressive individuals. Active music engagement appears particularly relevant for resilience among healthy individuals, while music-based coping may provide a stronger resource for those with depression. These findings offer promising directions for future research and may inform clinical applications involving music as a resilience-supportive resource.